2009
DOI: 10.1007/s00586-009-1018-5
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the reproducibility of ultrasound measures of abdominal muscle activation in patients with chronic non-specific low back pain

Abstract: Ultrasound (US) measures are used by clinicians and researchers to evaluate improvements in activity of the abdominal muscles in patients with low back pain. Studies evaluating the reproducibility of these US measures provide some information; however, little is known about the reproducibility of these US measures over time in patients with low back pain. The objectives of this study were to estimate the reproducibility of ultrasound measurements of automatic activation of the lateral abdominal wall muscles us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 29 publications
7
70
0
1
Order By: Relevance
“…These parameters are regarded quick and easy to obtain, non-invasive indicators of the TrA performance which is crucial for stability and control of the lumbar spine [2,3]. Authors conclude that US measurement of TrA thickness generally shows acceptable reliability in healthy persons [6][7][8][9][10][11][12][13][14][15][16] and patients with low back pain [12,[17][18][19][20][21][22]. Results concerning TrA thickness change are still contradictory or unclear.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…These parameters are regarded quick and easy to obtain, non-invasive indicators of the TrA performance which is crucial for stability and control of the lumbar spine [2,3]. Authors conclude that US measurement of TrA thickness generally shows acceptable reliability in healthy persons [6][7][8][9][10][11][12][13][14][15][16] and patients with low back pain [12,[17][18][19][20][21][22]. Results concerning TrA thickness change are still contradictory or unclear.…”
Section: Introductionmentioning
confidence: 97%
“…For measurements taken on the same day Costa et al [20] showed moderate intra-rater reliability, Kiesel et al [12] reported good intra-rater reliability, Koppenhaver et al [21] showed excellent intra-rater and good to excellent inter-rater reliability, and results from Mannion et al [19] ranged from poor to excellent.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The thickness of rectus abdominis was measured as the maximal width of a point 4-cm transverse from the navel, excluding tendinous intersections. Because the other three parts have overlapping organizations, they were measured at the same position (Ferreira, Ferreira, & Hodges, 2004;Leonardo, Chris, Jane, Paul, & Debra, 2009). We measured two thirds of line drawn horizontally from the height of the navel perpendicular to a vertical axillary line (Figure 4).…”
Section: Thickness Of Abdominal Musclesmentioning
confidence: 99%